Youth Employment Instability, True State Dependence and Adult Wage Inequality - Matthias Umkehrer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper examines recent trends in employment patterns on the labor market for youth and changing returns to early employment stability over the past four decades. True state dependence is identified by exploiting exogenous variation in aggregate labor market conditions induced by differences in the time already spent on the labor market when a recession occurs. The results indicate decreasing employment stability for youth since the late 1980s limited to the lower half of the employment distribution. Returns to early employment stability are estimated to be both statistically and economically significant: While one additional day of youth employment increases adult wages on average by 0.034% for cohorts graduating in the late 1980s, this effect has almost doubled to 0.066% for cohorts graduating in the late 1990s. Furthermore, instrumental variable quantile regressions reveal this impact to be mostly pronounced at the bottom of the adult wage distribution. Comparison of quantile effects suggest that changing patterns of this kind of true state dependence contribute to rising wage inequality between the 1980s and 1990s in the lower tail of the adult wage distribution.
Keywords: C21; J21; J31; 330